A disciplina nas organizações empresariais: um estudo à luz do pensamento de Michel Foucault - Nery, Sergio (2008)
This work aims at approaching and establishing a certain connection between Michel Foucault s investigations on the issue of power and its force relations on the disciplinary society and the administrative management practices and behaviors used in business organizations. In order to better understand this approach, we will focus on the employment of discipline on the workers everyday life as a control and surveillance device. Along this work, we will also use the thoughts of other authors, especially from other areas and, specifically from Business Administration, to demonstrate that discipline in business organizations is used by means of hierarchy to maximize efficiency (and consequently production), to optimize time and minimize costs, besides the social control, working mainly as a regulation of punishing practices